Bincang Jurnalistik untuk Meningkatkan Kemampuan Investigasi Mahasiswa UIN Walisongo Semarang - Siti Rohmah; Rosy Febriani Daud; Arianto . (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2026)
This community service program aimed to enhance the investigative journalism literacy of UIN Walisongo Semarang students through a Bincang Jurnalistik activity entitled “Learning Investigative Reporting”. The program was motivated by the need for students to develop critical analysis skills, the ability to filter information, and the competence to write accurate and data-based investigative news in the midst of the rapid digital information flow. The implementation method consisted of four stages: orientation and introduction, delivery of investigative journalism material, writing practice, and evaluation and reflection. The activity was held on November 25, 2024, at UIN Walisongo Campus 1 and was attended by 40 students from various study programs. The results showed an improvement in students’ understanding of investigative journalism principles, including the application of 5W+1H, data verification, and ethical considerations. During the practice session, most participants were able to produce simple investigative news articles that included facts, sources, and critical analysis, although some weaknesses in writing structure remained. Evaluation indicated that 85% of participants found the program beneficial and expressed motivation to continue developing their investigative skills. Therefore, this community service initiative contributed to shaping students to become more critical, media literate, and practically skilled in investigative journalism, while also strengthening the role of higher education in promoting media literacy in the digital era.